2021
DOI: 10.3389/fonc.2021.592529
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 TOF-PET-Based EUD Predicts Response Post Liver Radioembolizations Using Recommended Manufacturer FDG Reconstruction Parameters

Abstract: PurposeExplaining why 90Y TOF-PET based equivalent uniform dose (EUD) using recommended manufacturer FDG reconstruction parameters has been shown to predict response.MethodsThe hot rods insert of a Jaszczak deluxe phantom was partially filled with a 2.65 GBq 90Y - 300ml DTPA water solution resulting in a 100 Gy mean absorbed dose in the 6 sectors. A two bed 20min/position acquisition was performed on a 550ps- and on a 320ps- TOF-PET/CT and reconstructed with recommended manufacturer FDG reconstruction paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In fact, centimetric heterogeneity activity patterns are typically met in sphere radioembolization (see Fig. 1 in [ 10 ]). This explains why 90 Y TOF-PET-based EUD is able to rightly take into account the impact of the heterogeneity of the absorbed dose distribution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, centimetric heterogeneity activity patterns are typically met in sphere radioembolization (see Fig. 1 in [ 10 ]). This explains why 90 Y TOF-PET-based EUD is able to rightly take into account the impact of the heterogeneity of the absorbed dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…3 the 100 Gy curves shapes are not similar to those of the 50 Gy setup. (reprinted from [ 10 ], true EUD computation was extended down to 3.2 mm by the present authors) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study aiming at such a demonstration [ 17 ], contrarily to our expectations, the radiobiological voxel dosimetry provided only a negligible advantage with respect to the mean dose. However, recent papers seem to confirm the validity of the voxel approach in TARE dosimetry [ 18 , 19 ]. We therefore performed a critical analysis of our previous study [ 17 ], and the following flaws were identified.…”
Section: Introductionmentioning
confidence: 99%